The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2021
DOI: 10.3389/fbioe.2021.632753
|View full text |Cite
|
Sign up to set email alerts
|

Controlled Release Utilizing Initiated Chemical Vapor Deposited (iCVD) of Polymeric Nanolayers

Abstract: This review will focus on the controlled release of pharmaceuticals and other organic molecules utilizing polymeric nanolayers grown by initiated chemical vapor deposited (iCVD). The iCVD layers are able conform to the geometry of the underlying substrate, facilitating release from one- and two-dimensional nanostructures with high surface area. The reactors for iCVD film growth can be customized for specific substrate geometries and scaled to large overall dimensions. The absence of surface tension in vapor de… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(22 citation statements)
references
References 73 publications
0
21
0
Order By: Relevance
“… 29 Moreover, using a low fraction of crosslinker allows the properties of the copolymer film to closely align with those of the homopolymer grown from the monovinyl monomer. 34 In control samples, the homopolymers, denoted as p(PFOMA) and p(EGDMA), were prepared in the absence of either EGDMA or PFOMA, respectively. All polymer coatings had a thickness of approximately 1000 nm, which was determined based on pre-evaluation, and provided the best conditions for the iCVD setup in terms of preparation times (deposition rates were 15 nm min −1 ) and the final coating performance.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“… 29 Moreover, using a low fraction of crosslinker allows the properties of the copolymer film to closely align with those of the homopolymer grown from the monovinyl monomer. 34 In control samples, the homopolymers, denoted as p(PFOMA) and p(EGDMA), were prepared in the absence of either EGDMA or PFOMA, respectively. All polymer coatings had a thickness of approximately 1000 nm, which was determined based on pre-evaluation, and provided the best conditions for the iCVD setup in terms of preparation times (deposition rates were 15 nm min −1 ) and the final coating performance.…”
Section: Resultsmentioning
confidence: 99%
“…Such excellent chemical resistance of p(PFOMA- co -EGDMA) could be attributed to crosslinking which enhanced the overall durability. 34 …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that increasing the degree of crosslinking with EGDA improves mechanical properties. , We have previously shown that crosslinking with EGDA increases the mechanical strength of the porous pillared PMAA coating to prevent cracking of the coating after thermal annealing when deposited on flexible substrates such as polynorbornene rubber . For this study and for practical bioapplications, a limited degree of crosslinking is preferred to prevent dissolution while maintaining the properties of the primary polymer . After 5 min of EGDA and MAA monomer deposition, the MAA flow is stopped and the EGDA continues to flow for the first 15 min of polymerization to ensure sufficient crosslinking.…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, the coating technique should be sufficiently benign to avoid damage to the underlying nanostructures. The room-temperature initiated CVD (iCVD) thus represents a suitable option for orthogonal engineering, given its compatibility with over 70 functional monomers, outstanding conformality on ultrahigh aspect ratio nanostructures, and ability to deposit ultrathin (<10 nm) polymer films . Other characteristics of iCVD-synthesized ultrathin films, such as high retention of functional groups, adjustable degree of cross-linking, being solvent free, etc., further enables precision synthesis of the surface chemistry, controllable mechanical properties, and compatibility with solvent-sensitive substrates (such as paper-based devices). , …”
Section: Research Needs In Understanding Fundamental Bacteria–surface...mentioning
confidence: 99%